2010
DOI: 10.1021/np100112p
|View full text |Cite
|
Sign up to set email alerts
|

Withaferin A, a Cytotoxic Steroid from Vassobia breviflora, Induces Apoptosis in Human Head and Neck Squamous Cell Carcinoma

Abstract: As part of a program to discover drug leads from plant biodiversity, the present investigation was undertaken to explore the anticancer potential of compounds derived from selected Latin American plants. Bioassay-guided fractionation of a crude extract of the aerial parts of Vassobia breviflora led to the isolation of the withanolide-type steroidal lactone, withaferin A (1). This compound was tested for antiproliferative activity against the head and neck squamous cell carcinoma (HNSCC) cell lines, MDA1986, JM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
105
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(106 citation statements)
references
References 25 publications
0
105
0
1
Order By: Relevance
“…a For cell lines used, see text. Withanolides 6,[9][10][11][12][13][14]17,18,20,and 21 were inactive for all cell lines used (IC 50 > 10 μM). …”
Section: ■ Experimental Sectionmentioning
confidence: 93%
See 1 more Smart Citation
“…a For cell lines used, see text. Withanolides 6,[9][10][11][12][13][14]17,18,20,and 21 were inactive for all cell lines used (IC 50 > 10 μM). …”
Section: ■ Experimental Sectionmentioning
confidence: 93%
“…2,3,6 It has been reported that those withanolides displaying the most promising antitumor characteristics contain an α,β-unsaturated ketone in ring A, a 5β,6β-epoxy group in ring B, and a nine-carbon side chain with an α,β-unsaturated δ-lactone group. 10 The typical withanolide withaferin A (16) (Figure 1) contains these three moieties and has been shown in vitro and in vivo to suppress the growth of an array of tumor cells, including breast, pancreatic, prostate, lung, leukemia, and head and neck squamous cell carcinoma (HNSCC), by inducing apoptosis, 11 thus possessing potential application as an antiproliferative agent. As part of an ongoing study of withanolides from plant sources, 11,12 a library of 224 native plant extracts from the U.S. Great Plains was evaluated for cytotoxic activities against HNSCC and melanoma cell lines using the MTS viability assay.…”
mentioning
confidence: 99%
“…From the biogenetic origin, it is likely that type I compounds are precursors to the more advanced structural types II−XXII. Type I withanolides that display the most promising antiproliferative characteristics also contain Δ 2 -1-oxo-functionality in ring A, a 5β,6β-epoxy-group in ring B, and a nine-carbon side chain incorporating the δ-lactone functionality found in withaferin A 1 [17], withacnistin 59 [18,19], withanolide D 48 [20][21][22][23], withanolide E 36 [8,[24][25][26][27], and 4β-hydroxywithanolide E 37 (Fig. 4) [8,[24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Withaferin A 1 (Fig. 1) was shown to induce apoptosis in vitro and in vivo by suppressing the growth of an array of tumor cells, including breast, pancreatic, prostate, lung, leukemia, as well as various head and neck squamous cell carcinomas (HNSCCs) [17]. This compound has the potential for development as an antiproliferative agent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation